Geography and development : a world regional approach - Fisher, James A. (Columbus : C.E. Merrill Publication Co., 1989)
Increasing development in faraway places is leading to a more interdependent world. Rapid advances in transportation technology and electronic communication are speeding up commercial, cultural, eco-nomic, and political interaction among countries and regions. One outgrowth of these changes is a global economy, which depends on the efficient exchange of raw materials and manufactured goods all over the world. Another consequence is the international impact of local politics. For example, because of political and economic linkages, unrest in the Middle East affects Africa, Europe, the USSR, Japan, and the United States. In a sense, this movement toward global interdependence has made our world smaller and the study of it even more exciting. It certainly has underscored the need to study differences in physical and human geography from place to place. College students are in a unique position to increase their understanding of the world and to use that knowledge to benefit themselves and others.
Part One. Basic Concepts and Ideas -- Part Two. Anglo America -- Part Three. Western Europe -- Part Four. Eastern Europe and the Soviet Union -- Part Five. Japan and Australia/ New Zealand -- Part Six. Latin America -- Part Seven. Africa South of the Sahara -- Part Eight. The Middle East and North Africa -- Part Nine. Monsoon Asia.
Includes index.
Keywords: ECONOMIC DEVELOPMENT